Comparison of clinical aspects and Mantoux test in tuberculosis versus non-tuberculosis superficial lymphadenitis - Siti Nilawardhani; Helmi Lubis; Ridwan M Daulay; Gabriel Panggabean; Siti Mirhalina Hasibuan (Indonesian Pediatric Society, 2004)
Objective To investigate the clinical aspects and result of Man-toux test in superficial lymphadenitis caused by Mycobacteriumtuberculosis (MTB) compared to that caused by non-MTB organ-isms.Methods This was a cross sectional study conducted on 86 pa-tients aged between 3 months and 14 year-old with enlargementof the superficial lymph nodes, 43 with tuberculosis superficial lym-phadenitis (TSL) and 43 with non-tuberculosis superficial lymphad-enitis (NTSL). The diagnoses of TSL and NTSL were confirmed byhistopathological examination. Clinical symptoms and Mantoux testwere examined in this study.Results In the TSL group, most children (70%) were in the age of>5-14 year-old, while in the NTSL, most (46%) were 1-5 years old.The most frequent chief complaint in the TSL group was fever(37%), while in the NTSL group, cough (49%) (p=0.004). Failure tothrive and loss of appetite were more frequently found in the TSL(70% and 35%) compared to the NTSL group (0 and 3%) (p=0.004).Most enlarged nodes in TSL were multiple (67%), while in NTSL,solitary (72%) (p<0.001). There were no differences in the locationand distribution of enlarged nodes between the two groups. Thirty-one (72%) children in the TSL group had positive Mantoux test,while in the NTSL group were only 2(5%) (p<0.001).Conclusions Most children with TSL had fever as the chief com-plaint while those with NTSL had cough. Children with TSL hadfailure to thrive, loss of appetite, multiple nodes, and positive Man-toux test more frequently compared to NTSL ones